MAKNA SIMBOLIK DAN NILAI PENDIDIKAN KARAKTER DALAM TRADISI MAPPASSILI MASYARAKAT SUKU MAKASSAR BERBASIS KEARIFAN LOKAL (Karya Ilmiah Mahasiswa (KIMA), 2022)
This study aims to analyze the symbolic meaning and value of character education in the mappassili tradition of the Makassar tribal community based on local wisdom. This study uses a qualitative descriptive research method using Charles Sanders Pierce's semiotic analysis. The research data is in the form of meaning contained in the symbols used in the mappassili tradition in the Makassar tribal community and the value of character education. The source of the data in this study is the mapassili tradition of traditional Makassar weddings and people who have in-depth knowledge or insight about the mappassili event. The results of this study indicate that mappassili contains a symbolic meaning as self-cleanliness and purity, which aims to cleanse the soul and body of the bride and groom before entering the household ship, the symbols used in the mappassili event are: jakjakkang, leko' passili, leko' betel, incense, candles, kaluku, doe, lading, pammaja brown sugar, serikaya cake, umba-umba cake, cucur bayao cake, layer cake. The character education values ​​contained in the first mappassili tradition are religious education values, the second is social education values, and the third the value of cultural education.